Development of rice production sustainability index in MADA, Malaysia - Ajidasile, Oluwagbemisola Hannah (2015)
Despite government efforts towards self-sufficiency and sustainable rice production,paddy production is still faced with crucial constraints to attaining high yield in production. Currently, there is over dependence on agricultural chemicals in curtailing pest, insect and weeds in paddy production. The general objective was to develop the overall agricultural sustainability index of rice farmers. The specific objectives were (i) to determine the present production practices, (ii) create sustainability index of rice production, and (iii) to determine factors affecting the sustainability practices of the rice farmers. This study was conducted in MADA area of Peninsular Malaysia. Four hundred and two randomly selected rice farmers in MADA were surveyed by structured questionnaire supplemented with interview to elicit responses on their various agricultural practices. The data collected were on the demographic characteristics, farmers’ production practices, farmers’ rationale for (i) insect, disease and weed control, (ii) the fertilization process presently followed by MADA paddy farmers and its sustainable impact on the environment, economic and social practices of the farmers. Descriptive statistics were used to describe the present production practices of the rice farmers in the study area, the sustainability index were created by assigning scores to the practices and ordinary least square regression analysis, OLS was adopted in examining the factors affecting sustainability practices. The overall adjusted Agricultural Sustainability Index scores for the 402 farmers ranged from 30.38 to 76.04 (from a total possible range of 0 to 100), with mean of 49. The result indicated that age, level of education, farm size, IPM training were positively significant to sustainability level of the farmers while major occupation and age squared were negatively significant to the farmers sustainability level. The empirical result of the multiple regression analysis shows that there is a strong correlation (R = 0.902) between the factors affecting sustainability and those predicted by the regression model. Based on the findings, it can concluded that rice production is highly sustainable in the area and the strategy to help the paddy farmers understand the possible reasons for using less of external inputs were convincing for motivating the farmers to adopt sustainable practice in the MADA.